A realist review of best practices and contextual factors enhancing treatment of opioid dependence in Indigenous contexts - Rita Henderson; Ashley McInnes; Ava Danyluk; Iskotoah'ka Wadsworth; Bonnie Healy; Lindsay Crowshoe (BMC, 2023)
Abstract Objectives The objective of this study was to examine international literature to identify best practices for treatment of opioid dependence in Indigenous contexts. Methods We utilized a systematic search to identify relevant literature. The literature was analysed using a realist review methodology supported by a two-step knowledge contextualization process, including a Knowledge Holders Gathering to initiate the literature search and analysis, and five consensus-building meetings to focus and synthesize relevant findings. A realist review methodology incorporates an analysis of the complex contextual factors in treatment by identifying program mechanisms, namely how and why different programs are effective in different contexts. Results A total of 27 sources were identified that met inclusion criteria. Contextual factors contributing to opioid dependence described in the literature often included discussions of a complex interaction of social determinants of health in the sampled community. Twenty-four articles provided evidence of the importance of compassion in treatment. Compassion was evidenced primarily at the individual level, in interpersonal relationships based on nonjudgmental care and respect for the client, as well as in more holistic treatment programs beyond biophysical supports such as medically assisted treatment. Compassion was also shown to be important at the structural level in harm reduction policies. Twenty-five articles provided evidence of the importance of client self-determination in treatment programs. Client self-determination was evidenced primarily at the structural level, in community-based programs and collaborative partnerships based in trust and meaningful engagement but was also shown to be important at the individual level in client-directed care. Identified outcomes moved beyond a reduction in opioid use to include holistic health and wellness goals, such as improved life skills, self-esteem, feelings of safety, and healing at the individual level. Community-level outcomes were also identified, including more families kept intact, reduction in drug-related medical evacuations, criminal charges and child protection cases, and an increase in school attendance, cleanliness, and community spirit. Conclusions The findings from this realist review indicate compassion and self-determination as key program mechanisms that can support outcomes beyond reduced incidence of substance use to include mitigating systemic health inequities and addressing social determinants of health in Indigenous communities, ultimately healing the whole human being.